2015
DOI: 10.1260/1369-4332.18.12.2089
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Traditional Timber Mortise-Tenon Joints

Abstract: The inverted-trapezoid sectioned dovetail (ITSD) mortise-tenon joint was popular during the Chinese Song Dynasty. To investigate the particular features of the ancient wood joint, three 1:4 scaled models of a double-span timber frame with two exterior joints and an interior joint were fabricated according to the construction method commonly used in Chinese traditional wood structures, and tested subjected to fully reversed cyclic loading. Investigated were the mechanical properties of the ITSD mortise-tenon jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…e evaluation of the ultimate deformation capacity of wooden structures requires the use of test results. Although some test results have been reported in the literature [22][23][24], Yingxian Wood Pagoda requires the use of transplantation analysis of the results. ese areas will be studied in future repair research work.…”
Section: Repair Discussionmentioning
confidence: 99%
“…e evaluation of the ultimate deformation capacity of wooden structures requires the use of test results. Although some test results have been reported in the literature [22][23][24], Yingxian Wood Pagoda requires the use of transplantation analysis of the results. ese areas will be studied in future repair research work.…”
Section: Repair Discussionmentioning
confidence: 99%
“…Shi et al [5] used a synchronous loading technique to study the hysteresis behavior of a full-scale Chinese timber structure and revealed the effects of vertical loads and gaps in the mortise-tenon joint. Some tests on the timber frame with straight mortise-tenon joints [6,7] or with dovetail joints [8][9][10][11] have been conducted and the pulling-out of the tenon were frequently observed. Zhang [12] studied the seismic and lateral resistance of column-and-tie wooden buildings, the global slip of the framework and the slip of the column footing were observed.…”
Section: Introductionmentioning
confidence: 99%
“…ese characteristics have typically been exhibited through lateral loading tests of timber frames incorporating mortise and tenon joints [9][10][11][12][13], in which a vertical load is applied to the top of the columns to simulate a gravity load, and a lateral cyclic load is applied by a horizontal actuator using displacement control. In these tests, the hysteresis curves obtained have been relatively full, and the joints have displayed good deformation and energy dissipation ability.…”
Section: Introductionmentioning
confidence: 99%
“…In these tests, the hysteresis curves obtained have been relatively full, and the joints have displayed good deformation and energy dissipation ability. Generally, the failure mode of mortise and tenon joints has been found to be the pullout failure of the tenon [11][12][13].…”
Section: Introductionmentioning
confidence: 99%